Um modelo eficiente para o projeto completo de redes ópticas - Lima, Fabio de Oliveira (2010)
This dissertation presents a new mixed integer linear programming model for the design of optical communication networks. This is a extensive modeling, which includes the design of logical and physical topology, routing of traffic demands, in addition to routing and wavelength assignment. The formulation supports multiple connections between each pair of network nodes, whether in the physical or logic topology. In its basic version, the model minimizes installation cost of the physical network and the operating cost of the network designed. However, its formulation allows explore various metrics such as network congestion, which was used for comparison with literature. This work presents results of experiments in order to validate the efficiency of this formulation with respect to quality of solutions and computational performance of previous work on the same subject. Also presented is a new way to obtain lower bounds on congestion, with minor computational cost, whose efficiency contrasts with the alternate MILP formulations found in literature.